2016
DOI: 10.1177/0886260516651313
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of Intrusive Behavior and Stalking: Comparing LGBTIQ and Heterosexual Groups

Abstract: The present research employed a mixed-methods approach and quasi-experimental design to examine perceptions and experiences of intrusive behavior (comprising 47 individual intrusive activities) within individuals identifying as lesbian, gay, bisexual, transgender, intersex, or queer (LGBTIQ) with a matched (in terms of age, sex, and income) sample of individuals identifying as heterosexual (N = 214). Despite only minor differences between the LGBTIQ and heterosexual groups concerning perceptions of the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Stalking was also identified as a common component of IPV that is more prevalent in sexual minority relationships than in heterosexual relationships. Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stalking was also identified as a common component of IPV that is more prevalent in sexual minority relationships than in heterosexual relationships. Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Men were more likely than women to report engaging in stalking behavior after a breakup, according to one study that analyzed the phenomenon in a gay lesbian, bisexual, and transgender sample ( N = 165; Derlega et al, 2011). Sexual minority groups are also likely to report intrusive behaviors and stalking victimization than their heterosexual peers (35.5% vs. 15.0%; Sheridan et al, 2019). Other studies indicate a high prevalence of male same-gender stalking, ranging from 62% (Australian Bureau of Statistics, 2010), 50% (Budd & Mattinson, 2000), 41% (Baum et al, 2009) to 24% (Purcell et al, 2002) and as low 18% (Pathé et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Based on limited extant research, this pattern may hold true for stalking victimization as well. Authors of a recent Australian study found that LGBTIQ 1 participants were significantly more likely to experience stalking (35%) compared to heterosexual participants (15%) (Sheridan, Scott, & Campbell, 2019). However, participant sex, 2 which was measured as male , female , or other , was not a significant predictor (Sheridan, Scott, & Campbell, 2019).…”
Section: Stalking Victimization Of Lgbtq Personsmentioning
confidence: 99%
“…Previous research into experiences of hate-based abuse, violence and discrimination has identified that lesbian, gay, bisexual or transgender (LGBT) 1 individuals are disproportionately victimized. 2 Studies into discriminatory and hate-based violence in both Australia and the UK have found that sexuality and gender minority individuals experience high rates of intrusive behaviour, verbal abuse, and threats, as well as physical and sexual assault (see Guasp et al, 2013; Hillier et al, 2005; Rothman et al, 2011; Sheridan et al, 2016; Sterzing et al, 2017). This victimization is in turn associated with poor mental health and wellbeing, particularly for youth populations who are at higher risk of self-harm and suicide (Collier et al, 2013; Couch et al, 2007; Dragowski et al, 2011; Johnson et al, 2007; Nuttbrock et al, 2010; Perez-Brumer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%